Flexible copper-clad laminate and electronic device

By using a base film composed of a polyaryl sulfide-based resin and a high glass transition temperature or a high melting point thermoplastic resin, combined with a Ni alloy metal layer, the problem of insufficient adhesion and adhesion between the polyaryl sulfide-based resin and metal or other resins is solved, and high tensile properties, low dielectric properties, excellent adhesion and dimensional accuracy are achieved.

CN119753576APending Publication Date: 2025-04-04DIC CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411238009.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-28
Filing Date
2024-09-05
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, the polyarylene sulfide-based resin has low adhesion and adhesion to metals or other resins, and there are problems such as poor productivity during the production process.

Method used

The base film consisting of a polyaryl sulfide-based resin and a thermoplastic resin having a glass transition temperature of 140°C or above or above, combined with the first metal layer and the second metal layer formed of an alloy containing Ni, is used to improve the adhesion and dimensional accuracy of the base film and the metal layer through the production of a biaxial stretched film and the construction of a laminated plate.

Benefits of technology

The high tensile properties and low dielectric properties of the base film are achieved, the adhesion and dimensional accuracy of the metal layer and the base film are improved, and the problem of insufficient adhesion and adhesion in the prior art is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005028313160000051
    Figure BDA0005028313160000051
  • Figure BDA0005028313160000061
    Figure BDA0005028313160000061
  • Figure BDA0005028313160000062
    Figure BDA0005028313160000062
Patent Text Reader

Abstract

Provided are: a base film which has excellent stretchability, has a low dielectric constant in the resulting biaxially stretched film, and can exhibit excellent adhesion to a metal; a laminated plate which uses the base film and has good dimensional accuracy; and an electronic device which uses the laminated plate. The problem can be solved by using a laminate provided with a base film containing a polyarylene sulfide resin (A) and a thermoplastic resin (B) having a glass transition temperature of 140 DEG C or higher or a melting point of 230 DEG C or higher (excluding a polyarylene sulfide resin), a first metal layer, and a second metal layer, the base film containing a polyarylene sulfide resin (A) and a thermoplastic resin (B) having a glass transition temperature of 140 DEG C or higher or a melting point of 230 DEG C or higher (excluding a polyarylene sulfide resin). The first metal layer is formed on the surface of the base film and is composed of an alloy containing Ni, and the second metal layer is formed on the surface of the first metal layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminated board and an electronic device. The laminated board is formed by laminating a base film and a metal layer. The base film has excellent adhesion to the metal and low dielectric properties and is composed of a resin composition containing a polyarylene sulfide resin as a main component. Background Art

[0002] In recent years, in electronic devices such as personal computers and mobile terminals, with the high speed and large capacity of communication, the high frequency of electrical signals has been continuously developed, requiring a corresponding printed wiring board. In particular, the higher the frequency of the electrical signal, the greater the loss (attenuation) of the signal power, so it is necessary to reduce the loss (transmission loss) of the signal power. Regarding transmission loss, there are conductor loss on the metal layer side of the conductor and dielectric loss on the substrate side. In order to reduce conductor loss, since there is a characteristic that the signal flows on the surface of the conductor due to the skin effect in the high frequency region, it is preferred to reduce the surface roughness of the copper foil that becomes the conductor. On the other hand, in order to reduce dielectric loss, it is preferred that the low dielectric properties of resin substrates and adhesive materials are used. A flexible substrate composed of materials that meet these characteristics is required as a circuit substrate with less transmission loss.

[0003] Patent Document 1 discloses a double-layer flexible substrate in which a base metal layer is formed directly on an insulating film without an adhesive, and a copper conductor layer is formed on the base metal layer. Insulating films include polyimide films, polyamide films, polyester films, polytetrafluoroethylene films, polyphenylene sulfide films, polyethylene naphthalate films, and liquid crystal polymer films, but only polyimide is described in the examples, and no other insulating films are described, so the adhesion is unclear.

[0004] In addition, films using polyarylene sulfide resins represented by polyphenylene sulfide resin (PPS) are used for capacitors, insulation materials for motors, and heat-resistant belts due to their excellent heat resistance, flame retardancy, chemical resistance, and electrical insulation. Polyarylene sulfide resins have excellent dielectric properties compared to PI and PET, so they can be suitably used in the fields of FPC and FFC. However, polyarylene sulfide films generally have low adhesion and tightness to metals and other resins, and also have the problem of lack of reactivity with adhesives.

[0005] As an improvement to this, for example, Patent Document 2 describes a biaxially stretched film composed of a polyarylene sulfide resin and a thermoplastic resin different from the polyarylene sulfide resin, which is laminated on at least one surface of a metal plate. However, the laminate is a laminate formed by directly laminating a layer composed of a low-melting polyphenylene sulfide resin or a non-oriented polyphenylene sulfide sheet with a metal plate, and there is no description of directly bonding a biaxially stretched film composed of a polyarylene sulfide resin and a thermoplastic resin different from the polyarylene sulfide resin to a metal. In addition, it is necessary to perform co-extrusion of a layer composed of a low-melting polyphenylene sulfide resin, a polyarylene sulfide resin and a thermoplastic resin layer different from the polyarylene sulfide resin, or lamination with a non-oriented polyphenylene sulfide sheet, which has problems such as poor productivity.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2006-13152

[0009] Patent Document 2: Japanese Patent Application Publication No. 2007-276456 Summary of the invention

[0010] Problems to be solved by the invention

[0011] The present invention provides a base film having excellent stretchability, a low dielectric constant in the obtained biaxially stretched film, and excellent adhesion to metals, and a laminated plate having excellent dimensional accuracy using the base film.

[0012] Means for solving problems

[0013] The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that the above-mentioned problems can be solved by using a laminated plate having a base film, a first metal layer and a second metal layer, thereby completing the present invention. The base film contains a polyarylene sulfide-based resin (A) and a thermoplastic resin (excluding the polyarylene sulfide-based resin) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher (B), the first metal layer is formed on the surface of the base film and is composed of an alloy containing Ni, and the second metal layer is formed on the surface of the first metal layer.

[0014] That is, the present invention relates to the following [1] to

[13] .

[0015] [1] A laminate comprising: a base film comprising a polyarylene sulfide resin (A) and a thermoplastic resin (excluding the polyarylene sulfide resin) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher (B); a first metal layer formed on a surface of the base film and comprising an alloy containing Ni; and a second metal layer formed on a surface of the first metal layer.

[0016] [2] The laminate according to 1, wherein the base film is a biaxially stretched film.

[0017] [3] The laminate according to 1 or 2, wherein the dielectric constant of the base film is 3.3 or less.

[0018] [4] The laminate according to any one of 1 to 3, wherein the content of the polyarylene sulfide-based resin (A) is 51 to 97% by mass relative to 100% by mass of the total amount of the base film.

[0019] [5] A laminate according to any one of 1 to 4, wherein the thermoplastic resin (excluding polyarylene sulfide resin) having a glass transition temperature of 140°C or above or a melting point of 230°C or above comprises at least one polymer selected from the group consisting of polyphenylene ether resin, polycarbonate resin, polyether sulfone resin, polyphenylene sulfone resin, polyetherimide resin, polysulfone resin, and fluorine-containing resin.

[0020] [6] A laminate according to any one of 1 to 5, wherein the ratio of the blending amount of the thermoplastic resin (excluding polyarylene sulfide resin) (B) having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher is 3 to 49% by mass relative to the total amount of the base film (100% by mass).

[0021] [7] The laminated plate according to any one of 1 to 6, wherein the first metal layer composed of an alloy containing Ni is an alloy containing Ni and Cr, and the metal species constituting the second metal layer is a metal containing 90 mass % or more of Cu.

[0022] [8] The laminated plate according to any one of 1 to 7, wherein the first metal layer composed of an alloy containing Ni is an alloy containing Ni and Cr, and the proportion of Cr present in the alloy is 3 to 50 mass %.

[0023] [9] The laminate according to any one of 1 to 8, wherein the base film further contains a modified elastomer (C) to which a reactive group is imparted.

[0024]

[10] The laminate according to 9, wherein the modified elastomer (C) is composed of an olefin-based polymer having at least one functional group selected from the group consisting of epoxy groups and acid anhydride groups.

[0025]

[11] The laminate according to item 9 or 10, wherein the content of the modified elastomer (C) is in the range of 1 to 15% by mass relative to 100% by mass of the total amount of the base film.

[0026]

[12] The laminate according to any one of 1 to 11, wherein the base film further contains 0.01 to 5% by mass of a silane coupling agent (D), wherein the silane coupling agent (D) contains at least one functional group selected from an epoxy group, an amino group, and an isocyanate group.

[0027]

[13] The laminate according to any one of 1 to 12, wherein the average dispersion diameter of the thermoplastic resin (excluding polyarylene sulfide resin) (B) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher is 5 μm or less.

[0028]

[14] An electronic device using the laminate according to any one of 1 to 13.

[0029] Effects of the Invention

[0030] According to the present invention, a laminated plate can be provided, which has improved adhesion between a first metal layer formed on the surface of the base film and a second metal layer formed on the surface of the first metal layer, and has excellent dimensional accuracy, by using a base film having excellent stretchability and dielectric properties, which is composed of a resin composition containing a polyarylene sulfide-based resin (A) and a thermoplastic resin (excluding the polyarylene sulfide-based resin) (B) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher. DETAILED DESCRIPTION

[0031] Hereinafter, the mode for carrying out the present invention will be described in detail.

[0032] [Basement membrane]

[0033] The base film of the present invention is a base film obtained by kneading raw materials including at least a polyarylene sulfide resin (hereinafter sometimes referred to as "PAS resin") (A) and a thermoplastic resin (excluding the polyarylene sulfide resin) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher (hereinafter sometimes referred to as "thermoplastic resin") (B) using an extruder or the like to obtain a resin composition, and then biaxially stretching the resin composition. The details of the kneading method and the stretching method will be described later.

[0034] The base film contains at least a polyarylene sulfide resin (A) and a thermoplastic resin (excluding the polyarylene sulfide resin) (B) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher.

[0035] In order to impart functionality, stretchability, and toughness, the base film may contain a modified elastomer (C) to which a reactive group is imparted.

[0036] In this case, the base film may have a continuous phase and a dispersed phase, in which case the continuous phase includes a polyarylene sulfide resin, and the dispersed phase includes a thermoplastic resin (excluding a polyarylene sulfide resin) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher (B). It should be noted that the modified elastomer (C) exists on the surface of particles of the thermoplastic resin (B) (i.e., the interface between the matrix and the particles), inside the particles of the thermoplastic resin (B), or in the form of particles (dispersed phase) different from the particles of the thermoplastic resin (B).

[0037] The average dispersion diameter of the dispersed phase composed of the thermoplastic resin (B) is 5 μm or less, preferably 0.1 μm or more and 5 μm or less, and more preferably 0.2 μm or more and 3 μm or less. If the average dispersion diameter of the dispersed phase is within the range of 0.1 μm or more and 5 μm or less, the physical properties as an insulating substrate can be maintained, and a base film with excellent adhesion to metal can be obtained.

[0038] The base film of the present invention preferably has a dielectric constant of 3.3 or less and a dielectric loss tangent of 0.005 or less at a frequency of 5 GHz. Furthermore, it is more preferably a dielectric constant of 3.0 or less and a dielectric loss tangent of 0.004 or less. If the dielectric constant is 3.3 or less and the dielectric loss tangent is 0.005 or less, it can be suitably used in FPC-related products for high-frequency applications.

[0039] The thickness of the base film is not particularly limited as long as it is a thickness that can produce a copper-clad laminate, and is preferably within a range of 10 to 500 μm, and more preferably within a range of 20 to 300 μm, for example.

[0040] In addition, the present inventors believe that the modified elastomer (C) also functions as a compatibilizer for the PAS-based resin (A) and the thermoplastic resin (B), whereby the particles are finely dispersed in the matrix, thereby improving the mechanical strength of the film. Furthermore, the present inventors believe that by using the modified elastomer (C) in combination with a silane coupling agent, the adhesion between the matrix and the particles via the modified elastomer (C) is further improved, and the mechanical strength of the film is further improved.

[0041] The base film is preferably a biaxially stretched film obtained by biaxially stretching a sheet obtained by extrusion molding.

[0042] When the film is biaxially stretched, the PAS-based resin (A) constituting the matrix is ​​crystallized in a state where its molecular chains are stretched, so that a film having high dimensional accuracy can be obtained.

[0043] The stretching ratio of the biaxially stretched film in the longitudinal direction (MD direction) is preferably 1.5 to 4 times, more preferably 2.0 to 3.8 times.

[0044] The stretching ratio in the width direction (TD direction) of the biaxially stretched film is preferably 1.5 to 4 times, more preferably 2.0 to 3.8 times.

[0045] It should be noted that the ratio of the stretching ratio in the width direction (TD direction) of the biaxially stretched film to the stretching ratio in the length direction (MD direction) of the biaxially stretched film (width direction (TD direction) / length direction (MD direction)) is preferably 0.8 to 1.3, and from the perspective of easily balancing the physical properties in the length direction and the physical properties in the width direction, it is more preferably 0.9 to 1.2.

[0046] [Polyarylene sulfide resin (A)]

[0047] The polyarylene sulfide resin (A) (PAS resin (A)) is a main component of the base film and is a component having the function of imparting excellent heat resistance, chemical resistance, and dielectric properties to the film.

[0048] The PAS-based resin (A) is a polymer including, as a repeating unit, a structure in which an aromatic ring and a sulfur atom are bonded to each other (specifically, a structure represented by the following formula (1)).

[0049] [Chemistry 1]

[0050]

[0051] (In the above formula, R 1 Each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, a nitro group, an amino group, a phenyl group, a methoxy group, or an ethoxy group, and n each independently represents an integer of 1 to 4.)

[0052] Here, R in the structure represented by formula (1) 1 Preferably, all of them are hydrogen atoms. With this structure, the mechanical strength of the PAS-based resin (A) can be further improved. 1 Examples of the structure represented by formula (1) in which all the atoms are hydrogen atoms include the structure represented by formula (2) below (i.e., a structure in which the sulfur atom is bonded to the aromatic ring at the para position) and the structure represented by formula (3) below (i.e., a structure in which the sulfur atom is bonded to the aromatic ring at the meta position).

[0053] [Chemistry 2]

[0054]

[0055] Among them, the structure represented by formula (1) is preferably a structure represented by formula (2). When the PAS-based resin (A) has a structure represented by formula (2), heat resistance and crystallinity can be further improved.

[0056] The PAS-based resin (A) may contain not only the structure represented by the above formula (1) but also the structures represented by the following formulae (4) to (7) as repeating units.

[0057] [Chemistry 3]

[0058]

[0059] The structures represented by formulae (4) to (7) preferably account for 30 mol% or less, more preferably 10 mol% or less of all repeating units constituting the PAS resin (A). This structure can further improve the heat resistance and mechanical strength of the PAS resin (A).

[0060] The bonding form of the structures represented by formulae (4) to (7) may be either random or block.

[0061] The PAS-based resin (A) may contain a trifunctional structure represented by the following formula (8), a naphthyl sulfide structure, or the like as a repeating unit in its molecular structure.

[0062] [Chemistry 4]

[0063]

[0064] The structure represented by formula (8), naphthyl sulfide structure, etc. are preferably contained in an amount of 1 mol% or less in all repeating units constituting the PAS-based resin (A), and more preferably are substantially not contained. This structure can reduce the chlorine atom content in the PAS-based resin (A).

[0065] The properties of the PAS-based resin (A) are not particularly limited unless the effects of the present invention are impaired, but the melt viscosity (V6) at 300° C. is preferably 100 to 2000 Pa·s, and more preferably 120 to 1600 Pa·s from the perspective of achieving a good balance between fluidity and mechanical strength.

[0066] Furthermore, it is particularly preferred that the PAS resin (A) has a peak in the molecular weight range of 15,000 to 40,000, and the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) is in the range of 5 to 10, and the non-Newtonian index is in the range of 0.9 to 1.3 in the measurement using gel permeation chromatography (GPC). By using this PAS resin (A), the chlorine atom content in the PAS resin (A) itself can be reduced to the range of 500 to 2,000 ppm without reducing the mechanical strength of the film, and it is easy to apply to halogen-free electronic / electrical parts.

[0067] In this specification, the weight average molecular weight (Mw), the number average molecular weight (Mn) and the molecular weight distribution (Mw / Mn) are respectively the values ​​measured by gel permeation chromatography (GPC). The measurement conditions of GPC are as follows.

[0068] [Measurement conditions of gel permeation chromatography]

[0069] Equipment: Ultra-high temperature polymer molecular weight distribution measuring device (SSC-7000 manufactured by Sensyuu Scientific Co., Ltd.)

[0070] Column: UT-805L (Showa Denko Co., Ltd.)

[0071] Column temperature: 210℃

[0072] Solvent: 1-Chloronaphthalene

[0073] Determination method: Molecular weight distribution and peak molecular weight were determined with a UV detector (360 nm) using 6 monodisperse polystyrenes for calibration.

[0074] The method for producing the PAS resin (A) is not particularly limited, and examples thereof include: 1) a method of polymerizing the dihalogenated aromatic compound in the presence of sulfur and sodium carbonate, and adding a polyhalogenated aromatic compound or other copolymerization component as needed; 2) a method of polymerizing the dihalogenated aromatic compound in the presence of a sulfiding agent, etc., and adding a polyhalogenated aromatic compound or other copolymerization component as needed; 3) a method of self-condensing the dihalogenated aromatic compound by adding p-chlorothiophenol and adding other copolymerization components as needed. Among these production methods, the method 2) is universal and is a preferred method.

[0075] During the reaction, an alkali metal salt of a carboxylic acid or a sulfonic acid or an alkali hydroxide may be added in order to adjust the degree of polymerization.

[0076] Among the above-mentioned method 2), the following method 2-1) or method 2-2) is particularly preferred.

[0077] In the method 2-1), an aqueous sulfiding agent is introduced into a mixture containing a heated organic polar solvent and a dihalogenated aromatic compound at a rate capable of removing water from the reaction mixture, and a dihalogenated aromatic compound and a sulfiding agent are added to the organic polar solvent. A polyhalogenated aromatic compound is added as required, and during the reaction, the amount of water in the reaction system is controlled to be in the range of 0.02 to 0.5 mol relative to 1 mol of the organic polar solvent, thereby producing a PAS-based resin (A) (see Japanese Patent Publication No. 07-228699).

[0078] In the method 2-2), a dihalogenated aromatic compound and, as required, a polyhalogenated aromatic compound or other copolymer components are added in the presence of a solid alkali metal sulfide and an aprotic polar organic solvent, and when the alkali metal hydrosulfide and the organic acid alkali metal salt are reacted, the amount of the organic acid alkali metal salt is controlled to be in the range of 0.01 to 0.9 mol relative to 1 mol of the sulfur source, and the amount of water in the reaction system is controlled to be in the range of 0.02 mol or less relative to 1 mol of the aprotic polar organic solvent, thereby producing a PAS-based resin (A) (see WO2010 / 058713 pamphlet).

[0079] Specific examples of the dihalogenated aromatic compound include p-dihalobenzene, m-dihalobenzene, o-dihalobenzene, 2,5-dihalotoluene, 1,4-dihalonaphthalene, 1-methoxy-2,5-dihalobenzene, 4,4'-dihalobiphenyl, 3,5-dihalobenzoic acid, 2,4-dihalobenzoic acid, 2,5-dihalonitrobenzene, 2,4-dihalonitrobenzene, 2,4-dihaloanisole, p,p'-dihalodiphenyl ether, 4,4'-dihalobenzophenone, 4,4'-dihalodiphenyl sulfone, 4,4'-dihalodiphenyl sulfoxide, 4,4'-dihalodiphenyl sulfide, and compounds having an alkyl group having 1 to 18 carbon atoms on the aromatic ring of each of the above compounds.

[0080] Examples of the polyhalogenated aromatic compound include 1,2,3-trihalobenzene, 1,2,4-trihalobenzene, 1,3,5-trihalobenzene, 1,2,3,5-tetrahalobenzene, 1,2,4,5-tetrahalobenzene, and 1,4,6-trihalonaphthalene.

[0081] It should be noted that the halogen atom contained in the above-mentioned compound is preferably a chlorine atom or a bromine atom.

[0082] The reaction mixture containing the PAS-based resin (A) obtained in the polymerization step can be post-treated by a known and commonly used method. The post-treatment method is not particularly limited, and examples thereof include the following methods (1) to (5).

[0083] In the method (1), after the polymerization reaction is completed, the reaction mixture is first distilled to remove the solvent under reduced pressure or normal pressure directly or after adding an acid or a base. The solid matter after the solvent is distilled off is then washed once or twice with water, a reaction solvent (or an organic solvent having an equivalent solubility for the low molecular weight polymer), acetone, methyl ethyl ketone, an alcohol or the like, and then further neutralized, washed with water, filtered and dried.

[0084] In the method (2), after the polymerization reaction is completed, a solvent such as water, acetone, methyl ethyl ketone, alcohols, ethers, halogenated hydrocarbons, aromatic hydrocarbons, aliphatic hydrocarbons, etc. (a solvent that is soluble in the polymerization solvent used and is at least a poor solvent for the PAS-based resin (A)) is added to the reaction mixture as a precipitant to precipitate solid products such as the PAS-based resin (A) and inorganic salts, which are then filtered, washed, and dried.

[0085] In the method (3), after the polymerization reaction is completed, a reaction solvent (or an organic solvent having an equivalent solubility for the low molecular weight polymer) is added to the reaction mixture and stirred, and the low molecular weight polymer is filtered out and then washed once or twice or more with water, acetone, methyl ethyl ketone, alcohol or the like solvent, and then neutralized, washed with water, filtered and dried.

[0086] In the method (4), after the polymerization reaction is completed, water is added to the reaction mixture to wash with water, filter, and if necessary, acid is added during the water washing to perform acid treatment, followed by drying.

[0087] In the method (5), after the polymerization reaction is completed, the reaction mixture is filtered, washed once or twice or more with a reaction solvent as necessary, further washed with water, filtered and dried.

[0088] Examples of the acid that can be used in the method (4) include saturated fatty acids such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, and monochloroacetic acid; unsaturated fatty acids such as acrylic acid, crotonic acid, and oleic acid; aromatic carboxylic acids such as benzoic acid, phthalic acid, and salicylic acid; dicarboxylic acids such as maleic acid and fumaric acid; organic acids such as sulfonic acids such as methanesulfonic acid and p-toluenesulfonic acid; and inorganic acids such as hydrochloric acid, sulfuric acid, sulfurous acid, nitric acid, nitrous acid, and phosphoric acid.

[0089] Examples of hydrogen salts include sodium hydrosulfide, disodium hydrogen phosphate, sodium hydrogen carbonate, etc. However, when used in an actual device, an organic acid that has little corrosion to metal parts is preferred.

[0090] In the above methods (1) to (5), the drying of the PAS-based resin (A) may be performed in a vacuum or in an atmosphere of an inert gas such as air or nitrogen.

[0091] In particular, the PAS resin (A) post-treated by the method (4) above can increase the amount of acid groups bonded to the molecular ends, and when mixed with a thermoplastic resin (B) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher and a modified elastomer (C), the dispersibility of these resins can be improved. The acid group is particularly preferably a carboxyl group.

[0092] The content of the PAS resin (A) as the main component in the base film is 51 to 97% by mass, preferably 60 to 95% by mass. If the content of the PAS resin (A) is within the above range, the film can be endowed with the original heat resistance and chemical resistance of the PAS resin, and the stretchability can also be maintained. It should be noted that the main component in the present invention refers to containing the specific resin at 50% by mass or more, preferably 60% by mass or more, relative to the total mass of the resin component used to form the base film.

[0093] [Thermoplastic resins having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher (excluding polyarylene sulfide resins) (B)]

[0094] The thermoplastic resin (excluding polyarylene sulfide resin) (hereinafter sometimes referred to as "thermoplastic resin") (B) of the present invention having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher may be any thermoplastic resin having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher.

[0095] As the thermoplastic resin (B), any thermoplastic resin (excluding polyarylene sulfide resins) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher may be used, and for example, various polymers such as polyphenylene ether resins, polycarbonate resins, polyether sulfone resins, polyphenyl sulfone resins, polyetherimide resins, polysulfone resins, and fluorine-containing resins, and blends containing at least one of these polymers may be used. Among them, polyphenylene ether and fluorine-containing resins are preferred from the viewpoint of low dielectric properties and miscibility with PAS.

[0096] The content of the thermoplastic resin (B) in the resin composition constituting the base film may be 3 to 49% by mass, preferably 5 to 40% by mass. The content of the thermoplastic resin (B) within the above range is effective in maintaining the physical properties of the base film and the adhesion to the metal layer.

[0097] The polyphenylene ether-based resin (hereinafter sometimes referred to as “PPE-based resin”) is a component having the function of lowering the dielectric constant and dielectric loss tangent of the base film.

[0098] The PPE-based resin is a polymer containing a structure represented by the following formula (9) as a repeating unit.

[0099] [Chemistry 5]

[0100]

[0101] In the above formula, R 2Each is independently a hydrogen atom, a halogen atom, a primary alkyl group having 1 to 7 carbon atoms, a secondary alkyl group having 1 to 7 carbon atoms, a phenyl group, a halogenated alkyl group, an aminoalkyl group, a hydrocarbyloxy group, or a halogenated hydrocarbyloxy group in which a halogen atom and an oxygen atom are separated by at least two carbon atoms; and m is independently an integer of 1 to 4.

[0102] Specific examples of PPE-based resins include homopolymers such as poly(2,6-dimethyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), and poly(2,6-dichloro-1,4-phenylene ether); and copolymers of 2,6-dimethylphenol and other phenols (for example, 2,3,6-trimethylphenol and 2-methyl-6-butylphenol).

[0103] Among them, the PPE-based resin is preferably poly(2,6-dimethyl-1,4-phenylene ether) or a copolymer of 2,6-dimethylphenol and 2,3,6-trimethylphenol, and more preferably poly(2,6-dimethyl-1,4-phenylene ether).

[0104] The number average molecular weight of the PPE-based resin is preferably 1,000 or more, more preferably 1,500 to 50,000, and even more preferably 1,500 to 30,000.

[0105] The fluorine-containing resin preferably has at least one reactive functional group selected from the group consisting of a carbonyl-containing group, a hydroxyl group, an epoxy group and an isocyanate group. These reactive functional groups may contain more than two kinds. Among them, from the aspect of excellent reactivity with the PAS-based resin (A), preferably a carbonyl-containing group. As the carbonyl-containing group, a group having a carbonyl group between the carbon atoms of the hydrocarbon group, a carbonate group, a carboxyl group, a haloformyl group, an alkoxycarbonyl group, an anhydride group, a polyfluoroalkoxycarbonyl group, etc. may be cited.

[0106] As methods for introducing reactive functional groups into fluorine-containing resins, the following methods can be cited: (1) when manufacturing the main chain of a fluorine-containing resin having a reactive functional group by polymerization reaction, a monomer having a reactive functional group is used; (2) a chain transfer agent that generates free radicals having a reactive functional group is used to manufacture a fluorine-containing resin having a functional group by polymerization reaction; (3) a polymerization initiator that generates free radicals having a reactive functional group is used to manufacture a fluorine-containing resin having a functional group by polymerization reaction; (4) a method of modifying the fluorine-containing resin by oxidation, thermal decomposition, etc. In addition, (5) a method of mixing a compound or resin that is compatible with the fluorine-containing resin and contains the functional group can be cited.

[0107] Examples of the reactive functional group-containing monomer include monomers having a carbonyl group, epoxy group-containing monomers, hydroxyl group-containing monomers, isocyanate group-containing monomers, and the like.

[0108] Examples of monomers having a carboxyl group include unsaturated dicarboxylic acids (maleic acid, itaconic acid, citraconic acid, crotonic acid, humic acid, 5-norbornene-2,3-dicarboxylic acid), their unsaturated dicarboxylic acid anhydrides, unsaturated monocarboxylic acids (acrylic acid, methacrylic acid), vinyl esters (vinyl acetate, vinyl chloroacetate, vinyl butyrate, vinyl pivalate, vinyl benzoate, vinyl crotonate), and the like.

[0109] Examples of the hydroxyl group-containing monomer include hydroxyl group-containing vinyl esters, hydroxyl group-containing vinyl ethers, hydroxyl group-containing allyl ethers, hydroxyl group-containing (meth)acrylates, hydroxyethyl crotonate, and allyl alcohol.

[0110] Examples of the epoxy group-containing monomer include unsaturated glycidyl ethers (allyl glycidyl ether, 2-methylallyl glycidyl ether, vinyl glycidyl ether, etc.) and unsaturated glycidyl esters (glycidyl acrylate, glycidyl methacrylate, etc.).

[0111] Examples of the isocyanate group-containing monomer include 2-(meth)acryloyloxyethyl isocyanate, 2-(2-(meth)acryloyloxyethoxy)ethyl isocyanate, and 1,1-bis((meth)acryloyloxymethyl)ethyl isocyanate.

[0112] The amount of reactive functional groups contained in the fluorine-containing resin is preferably 0.01 to 3 mol%, more preferably 0.03 to 2 mol%, and further preferably 0.05 to 1 mol% of all units constituting the fluorine-containing resin. If the amount of reactive functional groups is within the above range, the reactivity with the PAS-based resin is excellent and deterioration of fluidity can be suppressed.

[0113] The structure of fluorine-containing resin is not particularly limited, and comprises at least one fluoroolefin unit. For example, tetrafluoroethylene polymer, copolymers with perfluoro (alkyl vinyl ether), hexafluoropropylene, vinylidene fluoride, vinyl fluoride, trifluoroethylene, chlorotrifluoroethylene, and copolymers with fluorine-free non-fluorine ethylene monomers such as ethylene, propylene, butene, and alkyl vinyl ethers can also be cited. Specifically, polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-perfluoro (alkyl vinyl ether) copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene-hexafluoropropylene copolymer, polyvinylidene fluoride, polychlorotrifluoroethylene, etc. can be cited. Wherein, from the aspect of melt extrudability easy, preferably ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-perfluoro (alkyl vinyl ether) copolymer, tetrafluoroethylene-hexafluoropropylene copolymer.

[0114] The melting point of the fluorine-containing resin used in the present invention is not particularly limited, but is preferably 230° C. or higher, more preferably 270° C. or higher. When the melting point of the fluorine-containing resin is within the above range, heat resistance can be maintained and good melt extrusion stability can be achieved.

[0115] The glass transition temperature of the fluorine-containing resin used in the present invention is not particularly limited, but is 130°C or less, more preferably 120°C or less, or 110°C or less. If the fluorine-containing resin has the above-mentioned glass transition temperature, when a stretched film (a form of an insulating substrate) using a mixture with a PAS-based resin (A) is produced, peeling at the interface between the PAS-based resin (A) as a continuous phase and the fluorine-containing resin as a dispersed phase can be suppressed during stretching. Thus, breakage during stretching can be suppressed, and a film having excellent mechanical properties can be obtained.

[0116] [Modified elastomer (C)]

[0117] The modified elastomer (C) is a component having a reactive group capable of reacting with at least one of the PAS-based resin (A) and the thermoplastic resin (B) and thus has a function of improving the mechanical strength (toughness such as folding strength) of the film.

[0118] The reactive group of the modified elastomer (C) is preferably at least one selected from the group consisting of epoxy groups and acid anhydride groups, and more preferably epoxy groups. These reactive groups can react rapidly with the functional groups at the molecular terminals of the PAS-based resin (A) and the thermoplastic resin (B).

[0119] Examples of the modified elastomer (C) include copolymers comprising repeating units based on α-olefins and repeating units based on vinyl polymerizable compounds having the above functional groups, copolymers comprising repeating units based on α-olefins, repeating units based on vinyl polymerizable compounds having the above functional groups and repeating units based on acrylates, and the like.

[0120] Examples of the α-olefin include α-olefins having 2 to 8 carbon atoms, such as ethylene, propylene, and butene-1.

[0121] In addition, examples of the vinyl polymerizable compound having a functional group include α,β-unsaturated carboxylic acids and esters thereof such as acrylic acid, methacrylic acid, acrylic acid esters, and methacrylic acid esters, maleic acid, fumaric acid, itaconic acid, other unsaturated dicarboxylic acids having 4 to 10 carbon atoms, their mono- or diesters, their anhydrides, α,β-unsaturated dicarboxylic acids, their esters and their anhydrides, α,β-unsaturated glycidyl esters, and the like.

[0122] The α,β-unsaturated glycidyl ester is not particularly limited, and examples thereof include compounds represented by the following formula (10).

[0123] [Chemistry 6]

[0124]

[0125] In the above formula, R3 It is an alkenyl group having 1 to 6 carbon atoms.

[0126] Examples of the alkenyl group having 1 to 6 carbon atoms include ethenyl, 1-propenyl, 2-propenyl, 1-methylethenyl, 1-butenyl, 2-butenyl, 1-methyl-1-propenyl, 1-methyl-2-propenyl, 2-methyl-1-propenyl, 2-methyl-2-propenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, 1-methyl-1-pentenyl, 1-methyl-3-pentenyl, 1,1-dimethyl-1-butenyl, 1-hexenyl, and 3-hexenyl.

[0127] R 4 Each independently represents a hydrogen atom, a halogen atom, or an alkyl group having 1 to 6 carbon atoms.

[0128] Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom and an iodine atom.

[0129] Examples of the alkyl group having 1 to 6 carbon atoms include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, 2-methylbutyl, 3-methylbutyl, 2,2-dimethylpropyl, hexyl, 1-methylpentyl, 2-methylpentyl, 3-methylpentyl, 4-methylpentyl, 2,2-dimethylbutyl, 2,3-dimethylbutyl, 2,4-dimethylbutyl, 3,3-dimethylbutyl and 2-ethylbutyl.

[0130] Specific examples of the α,β-unsaturated glycidyl ester include glycidyl acrylate and glycidyl methacrylate, and glycidyl methacrylate is preferred.

[0131] The ratio of the repeating unit based on α-olefin in the modified elastomer (C) is preferably 50 to 95% by mass, more preferably 50 to 80% by mass. When the ratio of the repeating unit based on α-olefin is within the above range, the stretching uniformity and folding strength of the film can be improved.

[0132] In addition, the proportion of repeating units based on vinyl polymerizable compounds having functional groups in the modified elastomer (C) is preferably 1 to 30% by mass, more preferably 2 to 20% by mass. When the proportion of repeating units based on vinyl polymerizable compounds having functional groups is within the above range, not only the target improvement effect can be obtained, but also good extrusion stability can be obtained.

[0133] The content of the modified elastomer (C) in the base film is preferably 1 to 15% by mass, more preferably 2 to 10% by mass. When the content of the modified elastomer (C) is within the above range, the toughness of the film, such as folding strength, is significantly improved.

[0134] [Silane coupling agent]

[0135] In the present invention, a silane coupling agent is preferably used as a component having a function of improving the compatibility (interaction) between the PAS-based resin (A) and other components (thermoplastic resin (B), modified elastomer (C)), so that the dispersibility of other components in the PAS-based resin (A) is greatly improved, and a good morphology can be formed.

[0136] The silane coupling agent is preferably a compound having a functional group that can react with a carboxyl group. The silane coupling agent reacts with any one of the PAS resin (A), the thermoplastic resin (B) other than the polyarylene sulfide resin, and the modified elastomer (C) to firmly bond with them. As a result, the effect of the silane coupling agent can be more significantly exerted, and in particular, the dispersibility of the thermoplastic resin (B) other than the polyarylene sulfide resin and the modified elastomer (C) in the PAS resin (A) can be improved.

[0137] Examples of the silane coupling agent include compounds having an epoxy group, an isocyanate group, an amino group, or a hydroxyl group.

[0138] Specific examples of silane coupling agents include epoxy group-containing alkoxysilane compounds such as γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; γ-isocyanatepropyltrimethoxysilane, γ-isocyanatepropyltriethoxysilane, γ-isocyanatepropylmethyldimethoxysilane, γ-isocyanatepropylmethyldiethoxysilane, γ-isocyanatepropylethyl Alkoxysilane compounds containing isocyanate groups, such as dimethoxysilane, γ-isocyanatepropylethyldiethoxysilane, and γ-isocyanatepropyltrichlorosilane; alkoxysilane compounds containing amino groups, such as γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, and γ-aminopropyltrimethoxysilane; alkoxysilane compounds containing hydroxy groups, such as γ-hydroxypropyltrimethoxysilane and γ-hydroxypropyltriethoxysilane.

[0139] The content of the silane coupling agent in the base film is preferably 0.01 to 5% by mass, more preferably 0.05 to 2.5% by mass. When the content of the silane coupling agent is within the above range, the dispersibility of other components in the PAS-based resin (A) can be significantly improved.

[0140] [Styrene resin]

[0141] The base film may contain a styrene resin. In principle, the styrene resin is contained in the dispersed phase of the base film. It should be noted that the styrene resin has a particularly high compatibility with the polyphenylene ether resin, so it can be contained in a form compatible with or close to the polyphenylene ether resin. The above-mentioned styrene resin has the function of improving fluidity when melted. It should be noted that in this specification, "styrene resin" refers to a resin with a styrene monomer as the main monomer unit.

[0142] The above-mentioned styrene resin is not particularly limited, and polymers of styrene monomers can be cited. At this time, the styrene monomer is not particularly limited, and styrene and its derivatives can be cited. As the above-mentioned styrene derivatives, alkyl styrenes such as methyl styrene, dimethyl styrene, trimethyl styrene, ethyl styrene, diethyl styrene, triethyl styrene, propyl styrene, butyl styrene, hexyl styrene, heptyl styrene, and octyl styrene can be cited; halogenated styrenes such as fluorostyrene, chlorostyrene, bromostyrene, dibromostyrene, and iodostyrene; nitrostyrene; acetyl styrene; methoxy styrene, etc. These styrene monomers can be used alone or in combination of two or more.

[0143] Styrene resin can be a homopolymer of styrene monomers, or a copolymer formed by copolymerization of more than two kinds. For example, the copolymer of the unsaturated monomer with glycidyl and / or oxazoline groups and the monomer with styrene as the main component, the block copolymer obtained by copolymerizing styrene monomers with conjugated diene compounds, and the hydrogenated block copolymer obtained by further hydrogenation of the block copolymer can be listed. In addition, the rubber components such as polybutadiene, styrene-butadiene copolymers, polyisoprene, butadiene-isoprene copolymers can also be used as rubber modified styrene (high impact styrene).

[0144] In addition, the above-mentioned styrene-based resins may be used alone or in combination of two or more kinds.

[0145] [additive]

[0146] The base film may contain a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, a UV stabilizer, a lubricant, an antistatic agent, a colorant, a conductive agent, and the like as long as the effects of the present invention are not impaired.

[0147] <Method for producing resin composition>

[0148] The method for producing the base film is not particularly limited, and may include a method in which at least the PAS resin (A) and the thermoplastic resin (B) are uniformly mixed using a roller or a Henschel mixer, and then introduced into a twin-screw extruder for melt kneading. The melt kneading may be either or both of kneading in a shear flow field and kneading in an elongational flow field. The melt kneading is preferably carried out under the condition that the ratio of the discharge amount (kg / hr) of the kneaded material to the screw speed (rpm) (discharge amount / screw speed) is 0.02 to 0.2 (kg / hr·rpm).

[0149] The setting temperature during mixing is selected to be in the range of +5°C to 70°C, more preferably in the range of +10°C to 50°C, compared to the melting point of the resin with a higher melting point among the PAS-based resin (A), the thermoplastic resin (B) and the modified elastomer (C). When the setting temperature is lower than the melting point of these resins, the viscosity of the composition increases significantly due to the presence of a portion of the unmelted resin, and the load on the twin-screw extruder increases, which is not preferred in terms of production.

[0150] In more detail, it is preferred to put each component into a twin-screw extruder and perform melt kneading under the above-mentioned set temperature and the resin temperature in the wire die head is about 310°C. At this time, the discharge amount of the kneaded product is in the range of 5 to 50 kg / hr at a rotation speed of 250 rpm. In particular, from the viewpoint of improving the dispersibility of each component, the discharge amount of the kneaded product is preferably 20 to 35 kg / hr at a rotation speed of 250 rpm. Therefore, the ratio of the discharge amount (kg / hr) of the kneaded product to the screw rotation speed (rpm) (discharge amount / screw rotation speed) is more preferably 0.08 to 0.14 (kg / hr·rpm).

[0151] <Method for producing base film>

[0152] The method for manufacturing the base film is not particularly limited, and preferably a biaxially stretched film is formed by biaxially stretching the sheet obtained from the resin composition. If a biaxially stretched film is made, the PAS resin (A) constituting the matrix crystallizes in a state where its molecular chain is stretched, so a film with high dimensional accuracy can be obtained. In one embodiment of the film, the PAS resin (A) is used as a matrix (continuous phase), and particles (dispersed phase) of a thermoplastic resin (B) other than the PAS resin are dispersed in the matrix.

[0153] It should be noted that the modified elastomer (C) exists on the surface of the particles of the thermoplastic resin (B) (i.e., the interface between the matrix and the particles), inside the particles of the thermoplastic resin (B), or in the form of particles (dispersed phase) different from the particles of the thermoplastic resin (B).

[0154] In addition, the present inventors believe that the modified elastomer (C) also functions as a compatibilizer for the PAS-based resin (A) and the thermoplastic resin (B), and thus the particles are finely dispersed in the matrix, thereby suppressing film breakage during stretching, improving the mechanical strength (folding strength, etc.) of the biaxially stretched film, and improving the mechanical strength of the laminate. Furthermore, the present inventors believe that by using the modified elastomer (C) in combination with a silane coupling agent, the adhesion of the interface between the matrix and the particles through the modified elastomer (C) is further improved, and the mechanical strength (folding strength, etc.) of the biaxially stretched film and the laminate is further improved.

[0155] The base film is preferably a biaxially stretched film obtained by biaxially stretching an unstretched sheet obtained from a resin composition.

[0156] The biaxially stretched film may have at least one layer composed of the composition of the base film of the present invention as the outermost layer, and may be a biaxially stretched laminated film in which a layer composed of another resin composition is laminated directly or via an adhesive layer.

[0157] The method for producing the biaxially stretched laminated film used in the present invention is not particularly limited. For example, in the case of a laminated structure, the following coextrusion method can be cited: the resin or resin mixture used in each resin layer is heated and melted by different extruders, and laminated in a molten state in a target laminated structure by a coextrusion laminated die method, a feed block method, etc., and then formed into a sheet by inflation, a T-die-cooling roll method, etc. This coextrusion method can relatively freely adjust the ratio of the thickness of each layer, and can obtain an unstretched laminated sheet with excellent cost performance, so it is preferred.

[0158] The method for producing the unstretched sheet is as follows: First, the resin composition is dried at 140°C for 3 hours or more, and then introduced into an extruder heated to 280 to 320°C.

[0159] Then, the molten state passing through the extruder is discharged in the form of a sheet through a T-die.

[0160] Next, the kneaded product in a sheet form is brought into close contact with a cooling roll having a surface temperature of 20 to 50° C. and cooled to solidify. Thus, an unoriented, unstretched sheet is obtained.

[0161] Next, when biaxial stretching is performed, the unstretched sheet is biaxially stretched.

[0162] As the stretching method, a sequential biaxial stretching method, a simultaneous biaxial stretching method, or a method combining these methods can be used.

[0163] When biaxial stretching is performed by a sequential biaxial stretching method, for example, the obtained unstretched sheet is heated with a heating roller group, stretched to 1.5 to 4 times (preferably 2 to 3.8 times) in the length direction (MD direction) in one stage or more than two stages, and then cooled with a cooling roller group at 30 to 60°C.

[0164] The stretching temperature is preferably the glass transition temperature (Tg) of the PAS-based resin (A) to Tg+40°C, more preferably Tg+3°C to Tg+30°C, and even more preferably Tg+3°C to Tg+20°C.

[0165] Next, the film is stretched in the width direction (TD direction) by using a tenter. The film stretched in the MD direction is introduced into the tenter while holding both ends thereof with clips, and stretched in the TD direction.

[0166] It should be noted that the stretching ratio is preferably 1.5 to 4 times, and more preferably 2 to 3.8 times.

[0167] The stretching temperature is preferably Tg to Tg+40°C, more preferably Tg+3°C to Tg+30°C, and even more preferably Tg+3°C to Tg+20°C.

[0168] It should be noted that the ratio of the stretching ratio in the width direction (TD direction) of the biaxially stretched film to the stretching ratio in the length direction (MD direction) of the biaxially stretched film (width direction (TD direction)) / length direction (MD direction)) is preferably 0.8 to 1.2, and more preferably 0.9 to 1.1.

[0169] Next, the biaxially stretched film is thermally fixed while being stretched or relaxed in the width direction.

[0170] The heat setting temperature is not particularly limited, but is preferably 200 to 280°C, more preferably 220 to 280°C, and further preferably 240 to 275°C. It should be noted that the heat setting may be performed in two stages by changing the heat setting temperature. In this case, it is preferred that the heat setting temperature of the second stage is higher by +10°C to 40°C than the heat setting temperature of the first stage. The heat resistance and mechanical strength of the biaxially stretched film heat-set at the heat setting temperature within this range are further improved.

[0171] In addition, the heat setting time is preferably 1 to 60 seconds.

[0172] Furthermore, the biaxially stretched film is cooled while being relaxed in the width direction in a temperature range of 50 to 280° C. The relaxation rate is preferably 0.5 to 10%, more preferably 2 to 8%, and even more preferably 3 to 7%.

[0173] In order to improve thermal stability, the film of the present invention may be further heat treated. As the heat treatment method after stretching, for example, known methods such as a method of blowing hot air, a method of irradiating infrared rays, and a method of irradiating microwaves can be cited. Among them, the method of blowing hot air is preferred because it can be heated uniformly and with high precision.

[0174] The heat treatment temperature is preferably 150 to 260°C, more preferably 160 to 240°C.

[0175] The heat treatment time is preferably 3 seconds to 300 seconds, more preferably 5 seconds to 100 seconds.

[0176] The base film of the present invention may be subjected to treatment for improving the adhesiveness of its surface as required. Examples of methods for improving the adhesiveness include corona treatment, plasma treatment, acid treatment, and flame treatment.

[0177] As mentioned above, although the base film and the laminated plate of this invention were demonstrated, this invention is not limited to the structure of the said embodiment.

[0178] For example, the film and the laminated plate of the present invention may each have any other arbitrary configuration added to the configuration of the above-described embodiment, or may be replaced with any configuration that exhibits the same function.

[0179] [Laminated board]

[0180] The laminated plate of the present invention comprises the above-mentioned base film (preferably a biaxially stretched film or a biaxially stretched laminated film), a first metal layer formed on the surface of the above-mentioned base film, and a second metal layer formed on the surface of the first metal layer.

[0181] The laminated plate of the present invention may have a structure of metal layer (at least a conductive layer including a first metal layer and a second metal layer)-film, metal layer-film-metal layer, metal layer-film-metal layer-film, metal layer-metal layer-film, metal layer-metal layer-film, metal layer-metal layer-film-metal layer, etc. In addition, it may also have a structure formed by stacking a plurality of the above-mentioned laminated plates.

[0182] Since the base film of this laminate has excellent dielectric properties, it can be processed and used as a flexible printed wiring board (FPC) or a flexible flat cable (FFC) suitable for next-generation high-speed transmission.

[0183] Furthermore, when a biaxially stretched film having excellent stretching uniformity is used, the thickness uniformity of the laminated plate is excellent, and the variation in the dielectric constant thereof can be suppressed.

[0184] Furthermore, an intermediate layer having a function of improving the adhesion between the film and the metal layer may be provided, for example.

[0185] [First metal layer]

[0186] The first metal layer can be provided by forming a metal layer on the surface of a base film containing at least a polyarylene sulfide resin (A) and a thermoplastic resin (excluding the polyarylene sulfide resin) (B) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher. The first metal layer has a function of improving the adhesion between the base film and the second metal layer or the copper plating layer.

[0187] The first metal layer can be formed of Ni, Cu, Cr or an alloy of one or more of these metals. From the perspective of improving the adhesion between the base film and the second metal layer or the copper plating layer, it is preferred to use an alloy containing at least Ni or Ni and Cr.

[0188] That is, the ratio of Ni present in the first metal layer is preferably in the range of 10 mass % to 97 mass %, and more preferably in the range of 30 mass % to 95 mass %.

[0189] Furthermore, when the first metal layer contains Cu, the ratio of Cu present in the first metal layer is preferably in the range of 5 mass % to 90 mass %, and more preferably in the range of 20 mass % to 70 mass %.

[0190] Furthermore, when the first metal layer contains Cr, the ratio of Cr present in the first metal layer is preferably in the range of 3 mass % to 50 mass %, and more preferably in the range of 5 mass % to 40 mass %.

[0191] When Ni and Cr are contained in the first metal layer, the ratio of Ni is preferably in the range of 50 to 97 mass %, and the ratio of Cr is preferably in the range of 3 to 50 mass %.

[0192] The thickness of the first metal layer is not particularly limited, but is preferably within a range of 1 to 500 nm, more preferably within a range of 5 to 100 nm.

[0193] Regarding the thickness of the first metal layer, the thickness determined by XPS or TEM may be used, or the thickness may be estimated based on the film formation rate by sputtering.

[0194] When estimating the thickness from the film formation rate of sputtering, sputtering of 0.1 μm (100 nm) or more is performed at an arbitrary film formation rate, and measurement can be performed from the relationship between the sputtering time and the sputtered thickness.

[0195] The first metal layer can be formed on the surface of the base film as long as it can be formed on at least one side of the base film, or it can be formed on both sides. In addition, when the first metal layer is provided on both sides of the base film, the sputtering process can be performed on one side one by one, or on both sides at once.

[0196] [Step of Forming the First Metal Layer]

[0197] In the step of forming the first metal layer, a metal layer is formed by sputtering on the surface of a base film containing a polyarylene sulfide resin (A) and a thermoplastic resin (B) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher.

[0198] The first metal layer may be formed of an alloy containing Ni, or Ni and one or more of Cu or Cr metals, and is preferably an alloy containing Ni and Cu, or Ni and Cr.

[0199] The first metal layer can be formed on the surface of the base film as long as it can be formed on at least one side of the base film, or it can be formed on both sides. In addition, when the first metal layer is provided on both sides of the base film, the sputtering process can be performed on one side one by one, or on both sides at once.

[0200] As a method for forming the first metal layer, a known and commonly used method can be adopted, for example, a DC magnetron sputtering method can be adopted. In addition, as an apparatus for forming the first metal layer, a film can be formed by a single-sheet sputtering apparatus or a roll-to-roll sputtering apparatus.

[0201] [Second metal layer]

[0202] The second metal layer can be provided by forming a metal layer on the surface of the first metal layer. The second metal layer functions as a conductive layer when a copper plating layer is subsequently provided. By providing the second metal layer, the deviation of the surface resistance value can be suppressed, and the deviation of the film thickness can be reduced during the subsequent copper plating.

[0203] It is preferred that the second metal layer is formed of an alloy containing Cu, and the ratio of Cu present in the second metal layer is 90 mass % or more.

[0204] The thickness of the second metal layer is not particularly limited, but is preferably within a range of 1 to 50 μm, more preferably within a range of 5 to 30 μm.

[0205] Regarding the thickness of the second metal layer, the thickness determined by XPS or TEM may be used, or the thickness may be estimated based on the film formation rate by sputtering.

[0206] When estimating the thickness from the film formation rate of sputtering, sputtering of 0.1 μm (100 nm) or more is performed at an arbitrary film formation rate, and measurement can be performed from the relationship between the sputtering time and the sputtered thickness.

[0207] The second metal layer can be formed on the surface of the first metal layer, and the metal layer can be formed on at least one side of the first metal layer, or on both sides. In addition, when the second metal layer is provided on both sides of the base film, the sputtering process or plating process can be performed on one side or on both sides at once.

[0208] [Step of Forming the Second Metal Layer]

[0209] In the step of forming the second metal layer, a metal layer is formed on the surface of the first metal layer. The second metal layer is preferably formed of an alloy having a Cu ratio of 90 mass % or more.

[0210] The thickness of the second metal layer is not particularly limited, but is preferably within a range of 1 nm to 50 μm, and more preferably within a range of 5 nm to 30 μm.

[0211] The thickness of the second metal layer can also be estimated in the same manner as the thickness of the first metal layer.

[0212] When the base film has the first metal layer on both surfaces, the second metal layer may be provided on one surface individually by sputtering or plating, or on both surfaces at once by sputtering or plating.

[0213] As a method for forming the second metal layer, a well-known and commonly used method can be adopted, for example, an electroless plating method, an electrolytic plating method, a vapor deposition method, a DC magnetron sputtering method, etc. When the DC magnetron sputtering method is adopted, as an apparatus for forming the second metal layer, a single-sheet sputtering apparatus or a roll-to-roll sputtering apparatus can be used for film formation.

[0214] [Copper plating]

[0215] The second metal layer constituting the laminate of the present invention may be a copper plating layer, or may have a structure in which a copper plating layer is further formed on the surface of the second metal layer. For example, when the laminate is used for a printed wiring board, the layer is provided for the purpose of forming a wiring pattern with high reliability that does not cause disconnection for a long time and can maintain good electrical conductivity.

[0216] The copper plating layer of the present invention is a layer formed on the surface of the first metal layer or the surface of the second metal layer, and as a method for forming the copper plating layer, it is preferably formed by a plating treatment. As the plating treatment, wet plating methods such as electrolytic plating and electroless plating methods that can easily form the copper plating layer can be listed. In addition, these plating methods can also be combined with more than two kinds. For example, after implementing electroless plating, electrolytic plating can also be implemented to form the copper plating layer.

[0217] The electroless plating method is, for example, a method of bringing an electroless plating solution into contact with a metal constituting the first metal layer or the second metal layer to deposit a metal such as copper contained in the electroless plating solution to form an electroless plating layer (film) composed of a metal film.

[0218] Examples of the plating solution used in the electroless plating include a plating solution containing Cu, a reducing agent, an aqueous medium, an organic solvent or other solvent.

[0219] Examples of the reducing agent include dimethylaminoborane, hypophosphorous acid, sodium hypophosphite, dimethylaminoborane, hydrazine, formaldehyde, sodium borohydride, and phenol.

[0220] The electroless plating solution may contain monocarboxylic acids such as acetic acid and formic acid; dicarboxylic acid compounds such as malonic acid, succinic acid, adipic acid, maleic acid, and fumaric acid; hydroxycarboxylic acid compounds such as malic acid, lactic acid, glycolic acid, gluconic acid, and citric acid; amino acid compounds such as glycine, alanine, iminodiacetic acid, arginine, aspartic acid, and glutamic acid; organic acids such as aminopolycarboxylic acid compounds such as iminodiacetic acid, nitrilotriacetic acid, ethylenediaminediacetic acid, ethylenediaminetetraacetic acid, and diethylenetriaminepentaacetic acid, or soluble salts (sodium salts, potassium salts, ammonium salts, etc.) of these organic acids, amine compounds such as ethylenediamine, diethylenetriamine, and triethylenetetraamine, and the like, as needed.

[0221] The electrolytic plating method is, for example, a method in which an electrolytic plating solution is brought into contact with the surface of the metal constituting the first metal layer or the second metal layer, and electricity is applied thereto, thereby causing metal ions such as copper contained in the electrolytic plating solution to precipitate on the surface of the first metal layer or the second metal layer provided at the cathode, thereby forming an electrolytic plating layer (metal film).

[0222] Examples of the plating solution used in the electrolytic plating include a plating solution containing copper sulfide, sulfuric acid, and an aqueous medium. Specifically, examples include a plating solution containing copper sulfate, sulfuric acid, and an aqueous medium.

[0223] The electroless plating solution and the electrolytic plating solution are preferably used at a temperature within a range of 20 to 98°C.

[0224] The film thickness of the copper plating layer of the present invention can adopt any value as needed, but is preferably in the range of 1 μm to 50 μm, and more preferably in the range of 5 μm to 30 μm.

[0225] The film thickness of the copper plating layer of the present invention can be adjusted by controlling the treatment time, current density, the amount of plating additives used, etc. in the plating treatment step when forming the copper plating layer.

[0226] [Example]

[0227] Next, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0228] [Example 1]

[0229] <Manufacturing of base film>

[0230] 84.5% by mass of a polyphenylene sulfide resin (PPS resin) (A) (manufactured by DIC Corporation, linear type, melting point 280°C, melt viscosity (V6) 110 Pa·s at 300°C) as a polyarylene sulfide resin, 15% by mass of a polyphenylene ether resin (manufactured by Mitsubishi Engineering-Plastics, poly(2,6-dimethyl-1,4-phenylene ether), glass transition temperature 210°C) as a thermoplastic resin (B), and 0.5% by mass of 3-glycidoxypropyltriethoxysilane as a silane coupling agent were uniformly mixed in a tumbler to obtain a mixture.

[0231] In addition, the polyphenylene sulfide resin has a carboxyl group at the molecular terminal.

[0232] Hereinafter, polyphenylene sulfide resin is described as “PPS”, and 3-glycidoxypropyltriethoxysilane is described as “silane coupling agent”.

[0233] Next, the mixture obtained above was put into a twin-screw extruder with a vent (manufactured by Nippon Steel Works, Ltd., "TEX-30α"). Then, it was melt-extruded under the conditions of a discharge rate of 20 kg / hr, a screw speed of 300 rpm, a barrel setting temperature of 200° C. on the raw material supply port side, a barrel setting temperature of 280 to 320° C. on the other side, and a resin temperature of about 300° C. in the strand die, discharged in the form of strands, cooled with water at a temperature of 30° C., and cut to produce a resin composition.

[0234] Next, the resin composition was dried at 140° C. for 3 hours and then fed into a single screw extruder with a full-flight screw to be melted at 280 to 310° C. The molten resin composition was extruded from a T-die and then closely cooled with a cooling roll set at 40° C. to prepare an unstretched sheet.

[0235] Next, the unstretched sheet was biaxially stretched to 3.0×3.0 times at 100° C. using a batch biaxial stretching machine (manufactured by Imoto Seisakusho Co., Ltd.) to obtain a base film with a thickness of 50 μm. Furthermore, the obtained film was fixed to a mold frame and heat-fixed in an oven at 275° C. to produce a biaxially stretched film as a base film.

[0236] Furthermore, the obtained biaxially stretched film was left to stand in a heating furnace (corresponding to an annealing furnace) at 180° C. for 60 seconds and cooled to room temperature to obtain an annealed base film.

[0237] The average particle size of the particles in the produced base film was measured as follows.

[0238] Specifically, the manufactured biaxially stretched film was cut by ultrathin sectioning along (A) a direction parallel to the length direction and perpendicular to the film surface, and (B) a direction parallel to the width direction and perpendicular to the film surface. The cut surfaces (A) and (B) of the cut film were respectively photographed with a scanning electron microscope (SEM) at 2000 times, and the obtained images were enlarged to A3 size. Any 50 dispersed phases of the enlarged SEM photo were selected, and the maximum diameter of the dispersed phase of each fracture surface (A) and (B) was measured, and the two directional quantities of the cut surfaces (A) and (B) were combined to calculate the average diameter.

[0239] As a result, the average particle size of the particles in the biaxially stretched film was 1.0 μm.

[0240] In addition, the biaxially stretched film after cutting was subjected to SEM-EDS analysis to analyze the components of the matrix and particles constituting the base film. The results showed that the component constituting the matrix was PPS, and the component constituting the particles was PPE resin.

[0241] <Manufacturing of the First Metal Layer>

[0242] The obtained base film was cut into a width of 200 mm and a length of 200 mm and placed in a magnetron sputtering device. A sputtering cathode used an alloy target of Ni and Cr. The ratio (atomic percentage) of Cr in the target used was an alloy of 25 atomic % (22.8 mass %). A first metal layer consisting of an alloy of Ni and Cr was formed on the surface of the base film. Here, the thickness of the first metal layer was adjusted to 30 nm.

[0243] <Manufacturing of Second Metal Layer>

[0244] A second metal layer is formed on the surface of the first metal layer.

[0245] The base film with the first metal layer formed thereon was placed in a magnetron sputtering device. A Cu target was used as a sputtering cathode. A second metal layer made of Cu was formed on the surface of the base film. Here, the thickness of the second metal layer was adjusted to 80 nm.

[0246] <Production of copper plating>

[0247] Each sample was left in the room for 24 hours and then electroplated. As a pretreatment for electroplating, an acid treatment was performed at 30° C. using a 10 mass % sulfuric acid aqueous solution to remove copper oxide present on the surface of the second metal layer.

[0248] A copper plating film having a thickness of 12.0 μm was formed on the surface of the second metal layer by electrolytic plating to obtain a copper-clad laminate. Here, a copper plating solution containing copper sulfate, sulfuric acid, hydrochloric acid, and additives was used.

[0249] [Example 2]

[0250] A base film and a copper-clad laminate were produced by the same method as in Example 1 except that the thickness of the second metal layer was adjusted to 12 μm and no copper plating film was formed.

[0251] [Example 3]

[0252] A base film and a copper-clad laminate were produced in the same manner as in Example 1 except that 94.5% by mass of a PPS resin (A), 5% by mass of a polycarbonate resin (manufactured by Mitsubishi Engineering-Plastics Chemicals Co., Ltd., glass transition temperature 145°C, hereinafter sometimes referred to as "PC") as a thermoplastic resin (B), and 0.5% by mass of a silane coupling agent were used.

[0253] The average particle size of the particles in the biaxially stretched film was measured by the same method as in Example 1 and was found to be 1.3 μm.

[0254] Furthermore, the constituent components of the base film were analyzed by the same method as in Example 1. As a result, it was found that the PC resin particles were dispersed in the PPS matrix.

[0255] [Example 4]

[0256] A base film and a copper-clad laminate were produced in the same manner as in Example 1 except that 89.5% by mass of a PPS resin (A), 10% by mass of a polyethersulfone resin (manufactured by BASF Corporation, glass transition temperature 225°C, hereinafter sometimes referred to as "PES") as a thermoplastic resin (B), and 0.5% by mass of a silane coupling agent were used.

[0257] Furthermore, the average particle size of the particles in the biaxially stretched film was measured by the same method as in Example 1 and was found to be 1.2 μm.

[0258] Furthermore, the constituent components of the base film were analyzed by the same method as in Example 1. As a result, it was found that particles of the PES resin were dispersed in the PPS matrix.

[0259] [Example 5]

[0260] A base film and a copper-clad laminate were produced in the same manner as in Example 1 using 84.5% by mass of a PPS resin (A), 15% by mass of a polyphenylsulfone resin (manufactured by BASF Corporation, glass transition temperature 220°C, hereinafter sometimes referred to as "PPSU") as a thermoplastic resin (B), and 0.5% by mass of a silane coupling agent.

[0261] The average particle size of the particles in the biaxially stretched film was measured by the same method as in Example 1 and was found to be 1.1 μm.

[0262] Furthermore, the constituent components of the base film were analyzed by the same method as in Example 1. As a result, it was found that the particles of the PPSU resin were dispersed in the PPS matrix.

[0263] [Example 6]

[0264] A base film and a copper-clad laminate were produced in the same manner as in Example 1 except that 94.5% by mass of a PPS resin (A), 5% by mass of a polyetherimide resin (manufactured by SABIC Corporation, glass transition temperature 216° C., hereinafter sometimes referred to as “PEI”) and 0.5% by mass of a silane coupling agent were used.

[0265] The average particle size of the particles in the biaxially stretched film was measured by the same method as in Example 1 and was found to be 1.4 μm.

[0266] Furthermore, the constituent components of the base film were analyzed by the same method as in Example 1. As a result, it was found that particles of the PES resin were dispersed in the PPS matrix.

[0267] [Example 7]

[0268] A base film was produced in the same manner as in Example 1 except that 84.5% by mass of a PPS resin (A), 15% by mass of a polysulfone resin (manufactured by Solvay Co., Ltd., glass transition temperature 190° C., hereinafter sometimes referred to as “PSU”) as a thermoplastic resin (B), and 0.5% by mass of a silane coupling agent were used.

[0269] The average particle size of the particles in the biaxially stretched film was measured by the same method as in Example 1 and was found to be 1.3 μm.

[0270] Furthermore, the constituent components of the base film were analyzed by the same method as in Example 1. As a result, it was found that the particles of the PSU resin were dispersed in the PPS matrix.

[0271] [Example 8]

[0272] A base film was manufactured in the same manner as in Example 1 except that 84.5% by mass of a PPS resin (A), 15% by mass of a fluorine-containing resin having a functional group, namely EA-2000 (PFA type, manufactured by AGC Corporation, melting point 300°C, glass transition temperature 94°C, hereinafter sometimes referred to as "modified PFA"), and 0.5% by mass of a silane coupling agent were used.

[0273] The average particle size of the particles in the biaxially stretched film was measured by the same method as in Example 1 and was found to be 1.3 μm.

[0274] Furthermore, the constituent components of the base film were analyzed by the same method as in Example 1. As a result, it was found that the fluorine-containing resin was dispersed in the PPS matrix.

[0275] [Example 9]

[0276] A base film and a copper-clad laminate were produced in the same manner as in Example 1 except that 74.5% by mass of PPS resin (A), 10% by mass of PPE resin as the thermoplastic resin (B), 15% by mass of fluorine-containing resin EA-2000, and 0.5% by mass of a silane coupling agent were used.

[0277] [Example 10]

[0278] A base film and a copper-clad laminate were produced in the same manner as in Example 1 except that 85% by mass of the PPS resin (A) and 15% by mass of the PPE resin were used as the thermoplastic resin (B).

[0279] [Example 11]

[0280] A base film and a copper-clad laminate were manufactured in the same manner as in Example 1, except that 82.5% by mass of a PPS resin (A), 15% by mass of a modified PFA resin as a thermoplastic resin (B), 2% by mass of BONDFAST7L (manufactured by Sumitomo Chemical Co., Ltd., ethylene / glycidyl methacrylate / methyl acrylate = 70 / 3 / 27 (mass %), hereinafter sometimes referred to as "BF7L") as a modified elastomer having a reactive group (C), and 0.5% by mass of a silane coupling agent.

[0281] [Example 12]

[0282] A base film and a copper-clad laminate were produced in the same manner as in Example 8, except that an alloy target of Ni and Cu was used as the sputtering cathode of the first metal layer. The target used had an alloy having a Cu ratio (atomic percentage) of 60 atomic % (61.9 mass %).

[0283] [Example 13]

[0284] A base film and a copper-clad laminate were produced in the same manner as in Example 1 except that a Cu and Ti alloy target was used as a sputtering cathode for the second metal layer. The target used had an alloy having a Ti ratio (atomic percentage) of 5 atomic % (3.8 mass %).

[0285] [Comparative Example 1]

[0286] A base film and a copper-clad laminate were produced in the same manner as in Example 1 except that only the PPS resin (A) was charged into a vented twin-screw extruder (manufactured by The Nippon Steel Works, Ltd., “TEX-30α”).

[0287] [Comparative Example 2]

[0288] 84.5% by mass of PPS resin (A), 15% by mass of PPE resin as thermoplastic resin (B) and 0.5% by mass of silane coupling agent were uniformly mixed with a roller to obtain a mixture. Next, the obtained mixture was put into a twin-screw extruder with a vent (manufactured by Nippon Steel Works, Ltd., "TEX-30α"). Then, melt extrusion was performed under the conditions of a discharge rate of 20 kg / hr, a screw speed of 300 rpm, a barrel setting temperature of 200°C on the raw material supply port side, a barrel setting temperature of 280 to 320°C in addition, and a resin temperature of about 300°C in the strand die, and the strand was discharged in the form of strands, cooled with water at a temperature of 30°C, and cut to produce a resin composition.

[0289] Next, the resin composition was dried at 140°C for 3 hours, and then put into a single screw extruder with a full-thread screw and melted at 280-310°C. After the molten resin composition was extruded from the T die, it was tightly cooled with a cooling roller set at 40°C to produce an unstretched film with a thickness of 50 μm. The obtained unstretched film was fixed to a mold frame and heat-fixed in an oven at 275°C to produce a biaxially stretched film as a base film. Furthermore, a first metal layer, a second metal layer, and a copper plating layer were produced on the unstretched film in the same manner as in Example 1 to produce a copper-clad laminate.

[0290] [Comparative Example 3]

[0291] A base film and a copper-clad laminate were produced in the same manner as in Example 1 except that 84.5% by mass of a PPS resin, 15% by mass of a general-purpose polystyrene resin (manufactured by DIC Corporation, glass transition temperature 100°C, hereinafter sometimes referred to as "GPPS") as a thermoplastic resin (B), and 0.5% by mass of a silane coupling agent were used.

[0292] [evaluate]

[0293] 1. Stretchability

[0294] The success rate of obtaining a stretched film without breakage when biaxially stretching 30 unstretched sheets was performed.

[0295] ◎:More than 95%

[0296] 〇:More than 80%

[0297] ×: less than 80%

[0298] 2. Dielectric properties of base film

[0299] The dielectric constant and dielectric loss tangent were measured based on the cavity resonance method specified in JIS C 2565: 1992. Specifically, a strip of 3 mm in width and 150 mm in length was made from the base film. Then, the produced strip was left to stand for 24 hours in an environment of 23°C and 50% Rh, and then the dielectric constant and dielectric loss tangent at a frequency of 5 GHz were measured by the cavity resonance method using ADMS010c series (manufactured by IET Co., Ltd.).

[0300] 3. Initial tightness

[0301] A sample of 10 mm wide x 70 mm long was cut out from the electrolytically plated copper-clad laminate, and the test was performed according to the test method specified in JIS K6854: 1999. The adhesion strength between the copper foil and the base film produced by electrolytic plating was measured and evaluated according to the following criteria.

[0302] ◎: 6N / cm or more

[0303] ○: 5N / cm or more and less than 6N / cm

[0304] ×: less than 5N / cm

[0305] 4. Adhesion after heat resistance test

[0306] The electrolytically plated copper-clad laminate was heated at 260°C for 5 minutes and then allowed to stand at 24°C for 24 hours. A sample of 10 mm wide x 70 mm long was cut out and tested according to the test method specified in JIS K 6854: 1999. The adhesion strength between the copper foil produced by electrolytic plating and the base film was measured and evaluated according to the following criteria.

[0307] ◎: 5N / cm or more

[0308] ○: 3N / cm or more and less than 5N / cm

[0309] ×: less than 3N / cm

[0310] 5. Dimensional accuracy

[0311] A 200×250 mm sample was cut out from the copper-clad laminate, holes were drilled at 50 mm intervals, and the distance between the holes was measured using the upper left hole as a reference point. The distance between the holes was measured again after etching and heating at 150°C / 30 minutes, and the dimensional change was evaluated according to the following criteria.

[0312] ◎: Less than 0.1%

[0313] ○: 0.3% or less 0.1% or more

[0314] ×: 0.3% or more

[0315] The above results are shown in Tables 1 to 3.

[0316] [Table 1]

[0317]

[0318] *PAR: Polyarylene sulfide resin

[0319] PPS: Polyphenylene sulfide resin

[0320] PPE: Polyphenylene ether resin

[0321] PC: Polycarbonate resin

[0322] PES: Polyethersulfone resin

[0323] PPSU: Polyphenylsulfone resin

[0324] PEI: Polyetherimide resin

[0325] PSU: Polysulfone resin modified PFA: Modified perfluoroalkoxyalkane Ni: Nickel

[0326] Cr: Chromium

[0327] Cu: Copper

[0328] Ti: Titanium

[0329] [Table 2]

[0330]

[0331] [Table 3]

[0332]

[0333] [Table 4]

[0334]

[0335] *GPPS: general purpose polystyrene resin.

Claims

1. A laminated plate comprising: A base film comprising a polyarylene sulfide resin (A) and a thermoplastic resin (B) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher and excluding the polyarylene sulfide resin; a first metal layer formed on a surface of the base film and composed of an alloy containing Ni; and The second metal layer is formed on the surface of the first metal layer.

2. The laminate according to claim 1, wherein: The base film is a biaxially stretched film.

3. The laminated plate according to claim 1 or 2, wherein: The dielectric constant of the base film is 3.3 or less.

4. The laminated plate according to claim 1 or 2, wherein: The ratio of the compounding amount of the polyarylene sulfide-based resin (A) is 51 to 97% by mass based on 100% by mass of the total amount of the base film.

5. The laminated plate according to claim 1 or 2, wherein: The thermoplastic resin (B) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher and not including a polyarylene sulfide resin comprises at least one polymer selected from the group consisting of polyphenylene ether resins, polycarbonate resins, polyether sulfone resins, polyphenylene sulfone resins, polyetherimide resins, polysulfone resins, and fluorine-containing resins.

6. The laminated plate according to claim 1 or 2, wherein: The ratio of the compounding amount of the thermoplastic resin (B) excluding the polyarylene sulfide resin and having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher is 3 to 49% by mass based on 100% by mass of the total amount of the base film.

7. The laminated plate according to claim 1 or 2, wherein: The first metal layer composed of an alloy containing Ni is an alloy containing Ni and Cr, and the metal species constituting the second metal layer is a metal containing 90 mass % or more of Cu.

8. The laminated plate according to claim 1 or 2, wherein: The first metal layer composed of an alloy containing Ni is an alloy containing Ni and Cr, and the ratio of Cr existing in the alloy is 3 to 50 mass %.

9. The laminated plate according to claim 1 or 2, wherein: The base film further contains a modified elastomer (C) to which a reactive group is imparted.

10. The laminated plate according to claim 9, wherein: The modified elastomer (C) is composed of an olefin polymer having at least one functional group selected from the group consisting of epoxy groups and acid anhydride groups.

11. The laminated plate according to claim 9, wherein: The content of the modified elastomer (C) is in the range of 1 to 15% by mass based on 100% by mass of the total amount of the base film.

12. The laminated plate according to claim 10, wherein: The content of the modified elastomer (C) is in the range of 1 to 15% by mass based on 100% by mass of the total amount of the base film.

13. The laminated plate according to claim 1 or 2, wherein: The base film further contains 0.01 to 5 mass % of a silane coupling agent (D), wherein the silane coupling agent (D) contains at least one functional group selected from the group consisting of an epoxy group, an amino group, and an isocyanate group.

14. The laminated plate according to claim 1 or 2, wherein: The thermoplastic resin (B) having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher and excluding the polyarylene sulfide resin has an average dispersion diameter of 5 μm or less.

15. An electronic device using the laminate according to claim 1 or 2.

Citation Information

Patent Citations

  • Production of polyarylene sulfide polymer

    JP1995228699A

  • Two-layer flexible board and manufacturing method thereof

    JP2006013152A

  • Laminate

    JP2007276456A

  • Method for manufacturing polyarylene sulfide resin

    WO2010058713A1